Analisis Kemampuan Komunikasi Matematis Siswa dalam Menyelesaikan Soal PISA - Rif'atul Machmuda; Sarwo Edy; Sri Suryanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Mathematical communication is a fundamental ability that students must have in order to support the learning of mathematics education in the 21st century. The level of creativity, critical reasoning skills, as well as student independence by applying a learning framework that supports the development of students' mathematical communication skills is appropriate is PISA (Program for International Students Assessment). The purpose of this study is to describe students' mathematical communication skills based on Uncertainty and Data content and focuses on three students of class VIII - A UPT SMPN 4 Lamongan as research subjects. The research data was obtained through the results of daily tests used to categorize the three student subjects. Then the analysis carried out in the results of mathematical communication ability tests and interviews, using indicators of mathematical communication skills, namely, 1) Connecting items, pictures or original charts to mathematical thinking; 2) Describe thinking ideas, situations and mathematical relationships in written and oral ways; 3) Use the concept of terms, symbols, and structure-based mathematical notation to convey ideas; also 4) Make conclusions in writing and orally. The research findings show that there are variations in students' mathematical communication abilities, namely with low mathematical communication only fulfilling the second indicator. Students with moderate mathematical communication fulfill the first, second and third indicators. Students with high mathematical communication fulfill all indicators.